Intermanual Transfer of Learning in a Fine Manual Skill Task - Shirley Regina de Almeida Batista; Paula Rodrigues; Olga Vasconcelos
Abstract Intermanual Transfer of Learning (IMTL) is the ability to learn a certain skill in an easier way with one hand after that skill has been learnt by the opposite hand(1). This research aimed to investigate IMTL in a Fine Manual Dexterity (FMD) task in subjects presenting different Hand Preference (HP). The sample comprised 882 right and left-handers, both genders, aged 6 to 95 years old. The Dutch Handedness Questionnaire(2) was used to assess HP and the Purdue Pegboard Test(3) evaluated FMD. Direction and intensity of HP, Direction of Transfer (DT), gender, age and nationality were analyzed. IMTL changed according to DT and age, tending to be asymmetric, holding high values in the direction of Non-Preferred Hand (NPH) to Preferred Hand (PH). Children had got a higher IMTL rather than youngsters, adults and old adults with significant differences in adults.